GROWTH PATTERN AND BODY CONDITION OF TRYPAUCHEN VAGINA IN THE MEKONG DELTA, VIETNAM - Q. M. Dinh (Journal of Animal and Plant Sciences, 2016)
Trypauchen vagina is a potential commercial fish, but little is known about its growth pattern and body condition. This study aimed to understand its growth characteristics and condition factors during the dry (January–May) and wet (June–December) seasons. The data analysis was based on 328 specimens collected from May 2014 to April 2015. Sex ratio of this fish in the wet season was not significantly different from that in the dry season. Length-weight relationships were similar between female and male T. vagina as well as between dry and wet seasons, but differed between juveniles and mature fish. The slope of the length-weight regression was close to the isometric growth value of 3. The condition factors of this fish varied with seasonal change and fish size-classes, but they were similar in two genders and close to well-being value of 1. Trypauchen vagina showed isometric growth, adapted well, can become a potential fish for future aquaculture in this region, and provides useful information for our understanding on other gobies in monsoonal areas.
Keywords: Goby; isometric growth; length-weight relationship; condition factor